Evaluation of Islamic Economic Ethics on Job Hugging and Job Hopping Behavior Among Generation Z Workers: Evaluasi Etika Ekonomi Islam terhadap Perilaku Bertahan dan Berpindah Pekerjaan di Kalangan Pekerja Generasi Z - MISI ANGGRAINI; Duhriah; Helda Nusrida; Yulizain Putra (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
This study examines the contrasting employment behaviors of Generation Z job hugging and job hopping through the lens of Islamic economic ethics. Utilizing a qualitative approach, data were collected via in-depth interviews with 30 Generation Z workers across various sectors. The analysis focused on understanding the ethical considerations influencing their job stability and job mobility decisions. Results reveal a nuanced balance between the desire for career growth and the Islamic ethical principle of responsibility towards sustainable work engagement. The discussion highlights how Islamic economic ethics can guide Generation Z workers to navigate career challenges while maintaining ethical integrity. This research contributes to the literature on workplace ethics and Generation Z employment patterns within an Islamic framework.